2002
DOI: 10.2224/sbp.2002.30.1.95
|View full text |Cite
|
Sign up to set email alerts
|

The Marital Satisfaction Questionnaire for Older Persons: Factor Structure in a French Sample

Abstract: The factor structure of the Marital Satisfaction Questionnaire for Older Persons (Haynes et al., 1992) for a sample of elderly French persons was examined. For the sample as a whole, as well as for women and men separately, the fit between the French data and the structure postulated by Haynes et al. was satisfactory. The meaning of the Communication / Companionship factor was the same in France as in the U.S. It proved to be a broad factor that expresses satisfaction in a wide variety of marital areas. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…These findings corroborate previous studies (Fouquereau & Baudoin, 2002;Haynes et al, 1992) where Cronbach's alpha coefficients of .96 and .95, respectively, were obtained with U.S. and French elderly persons.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings corroborate previous studies (Fouquereau & Baudoin, 2002;Haynes et al, 1992) where Cronbach's alpha coefficients of .96 and .95, respectively, were obtained with U.S. and French elderly persons.…”
Section: Discussionsupporting
confidence: 92%
“…However, this result is interpretable in the context of the scientific literature (see, for example, Bowman, 1990;Caughlin, Huston, & Houts, 2000), which highlights the relation between the In the Spanish version, we observed that the items assessing the couple's communication loaded on a separate factor, distinct from the Compatibility/Affective Quality factor, which was thus labeled simply "Communication." This differed slightly from the findings by both Haynes et al (1992) and Fouquereau and Baudoin (2002), in the sense that in both studies (conducted in the United States and France, respectively) the items that measure communication loaded on the same factor as those that measure companionship and compatibility, in the scale they thus named Communication/Companionship. It should be further explored whether this finding may relate to cultural differences.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations